Effectiveness of Food Garden School on Eco-Literacy in Early Childhood Sustainability Concept - Rizquna Saputri, Rizquna; Waluyo, Edi (Universitas Pendidikan Ganesha, 2024)
This research describes an ideal approach to implementing eco-literacy education in early childhood, to improve their understanding of sustainability and environmental awareness. However, the reality on the ground shows several obstacles, such as limited time, a lack of facilities and infrastructure, and a lack of readiness from preschool facilities, which cause gaps in understanding among learners. This research presents an innovation by applying food garden school activities as the main approach to eco-literacy education in early childhood. The aim is to increase their understanding of sustainability and eco-literacy, develop practical skills in interacting with the real environment, and inspire positive behavioral changes towards the environment from an early age. The method used was quantitative research with a pre-experimental design using a one-group pretest-posttest design pattern without a control group. Data analysis techniques include normality tests using Shapiro-Wilk, paired t-test to test the effect of food garden school activities, and N-Gain test to measure improvement from pretest to posttest. This study showed a significant increase in eco-literacy understanding, with the Shapiro-Wilk value increasing from 0.298 in the pretest to 0.799 in the posttest. The results of the paired t-test showed a t-value of 21.37 with a p-value of 0.001. In addition, the N-gain achieved was 0.54. This study implies that the gardening program or food garden school can be an effective tool for teachers in improving students' understanding of eco-literacy in their learning process.